Efficacy assessment of prebiotic enriched camel milk along with various prebiotic combinations against metabolic syndrome using animal model - ASHRAF, Iram; IQBAL, Sanaullah; AHMED, Waqas; REHMAN, Habib ur (Food Science and Technology, 2023)
Metabolic syndrome (MetS) is a public health concern even in apparently healthy individuals. This study was conducted with the main objective to evaluate the potential role of prebiotic enriched camel milk (PECM) as a functional food, against different biomarkers of MetS in comparison to fresh camel milk (CM) and other prebiotic sources, i.e., chicory root powder (CRP) and galacto-oligosaccharides (GOS) in rat’s model. The MetS was induced through a high-fat diet and streptozotocin. The PECM, CM, CRP, and GOS were fed to rats for 8 weeks, and different biochemical parameters were measured on baseline (0th day), 20th day, and 40th day. Prebiotics were able to significantly reduce the concentration of low-density lipoprotein, triglycerides, total cholesterol, and glucose compared to the control group with PECM being the most effective of all groups, whereas liver enzymes (ALT, AST, and AP) were significantly reduced and antioxidants improved by CM and PECM than other prebiotics and control. Histopathology results revealed improvement in degeneration and hydropic atrophies in the hepatocytes of the treatment group. It is concluded that PECM is effective in the management of MetS biomarkers and can improve the parameters of hyperlipidemia, liver enzymes, antioxidants, and glycemic control.